2010
DOI: 10.1111/j.1360-0443.2010.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

The Global Diversion of Pharmaceutical Drugs
Non‐medical use and diversion of psychotropic prescription drugs in North America: a review of sourcing routes and control measures

Abstract: The distinct nature and heterogeneity make PPD diversion a complex and difficult target for interventions. Prescription monitoring programs (PMPs) appear to reduce overall PPD use, yet their impact on reducing diversion or non-medical use is not clear. Law enforcement is unlikely to reach PPD diversion effectively. Effective reduction will probably require reductions in overall PPD consumption volumes, although such will need to be accomplished without compromising standards of good medical (e.g. pain) care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 63 publications
3
59
0
1
Order By: Relevance
“…6,68 Further, surveys have shown that most people with NMPOU obtain their POAs by diversion or nonmedical sourcing from family or friends. 69 In this wider context, people with need or desire for NMPOU are unlikely to face too many barriers to find or gain access to POAs for such purposes.…”
Section: Discussionmentioning
confidence: 99%
“…6,68 Further, surveys have shown that most people with NMPOU obtain their POAs by diversion or nonmedical sourcing from family or friends. 69 In this wider context, people with need or desire for NMPOU are unlikely to face too many barriers to find or gain access to POAs for such purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that diversion of psychoactive prescription drugs involves original as well as falsified products and that diverted drugs have diverse origins, including personal prescriptions, drug theft, illegal Internet shopping as well as smuggling (Fischer et al, 2010;Fittler et al, 2013;Fountain et al, 2000;Inciardi et al, 2007;Lapyere-Mestre et al, 2014;Peirce et al, 2012;UN, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One important limitation of drug prescription and dispensing databases is that only personally prescribed drugs are covered, while the sources of abused drugs are diverse (84,117 (103,124). In the USA, by far the class of prescription drugs most commonly implicated in misuse and abuse are the opioid analgesics (such as oxycodone) (106,124).…”
Section: Pharmacoepidemiological Methods In Studies Of Psychoactive Pmentioning
confidence: 99%